Entrepreneurship in Grade 4 Elementary School Students (Examining the implementation of the Pancasila Student Profile Strengthening Project) - Firdaus, Rido; Utami, Ratnasari Dyah; Hadromi, Hadromi (Journal of Research and Educational Research Evaluation, 2023)
Education is the right of every Indonesian citizen, whose implementation is strengthened by the 12-year compulsory education program, and curriculum improvements from the 2013 curriculum. become an independent curriculum. This study aims to analyze the implementation of a project to strengthen Pancasila student profiles (P5) on the theme of entrepreneurship based on the independent curriculum for class IV SD Negeri 03 Bejen. This research uses a qualitative and descriptive approach. Data collection techniques used are interviews, observation and documentation. Test the validity of the data using source triangulation and triangulation techniques Data analysis techniques using qualitative data analysis include data collection activities, data reduction, data presentation, and the conclusions of the research results Based on the findings of the research results indicate that the process of planning, implementing and evaluating P5 at SD N 03 Bejen Karanganyar Regency has been carried out well. This can be seen in the planning, implementation, and evaluation.